2013
DOI: 10.1371/journal.pgen.1003765
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation between RUNX1-ETO9a and Novel Transcriptional Partner KLF6 in Upregulation of Alox5 in Acute Myeloid Leukemia

Abstract: Fusion protein RUNX1-ETO (AML1-ETO, RUNX1-RUNX1T1) is expressed as the result of the 8q22;21q22 translocation [t(8;21)], which is one of the most common chromosomal abnormalities found in acute myeloid leukemia. RUNX1-ETO is thought to promote leukemia development through the aberrant regulation of RUNX1 (AML1) target genes. Repression of these genes occurs via the recruitment of the corepressors N-COR and SMRT due to their interaction with ETO. Mechanisms of RUNX1-ETO target gene upregulation remain less well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 54 publications
3
20
0
Order By: Relevance
“…This is, at least partially, in contrast with our findings on the PML/RARadriven AML model, in which the genetic targeting of 5-LO did not replicate the effects of pharmacologic inhibition on the stem cell capacity. This is in accordance with recent findings showing full leukemogenic potential of AML-1/ ETOex9-expressing HSPCs in an Alox5 À/À background although an impairment of the in vitro self-renewal of HSPCs expressing either AML-1/ETOex9, PML/RARa or MLL/AF9 was seen (50). CML is a myeloproliferative disease characterized by proliferation of hematopoietic progenitors, which are still able to fully differentiate.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is, at least partially, in contrast with our findings on the PML/RARadriven AML model, in which the genetic targeting of 5-LO did not replicate the effects of pharmacologic inhibition on the stem cell capacity. This is in accordance with recent findings showing full leukemogenic potential of AML-1/ ETOex9-expressing HSPCs in an Alox5 À/À background although an impairment of the in vitro self-renewal of HSPCs expressing either AML-1/ETOex9, PML/RARa or MLL/AF9 was seen (50). CML is a myeloproliferative disease characterized by proliferation of hematopoietic progenitors, which are still able to fully differentiate.…”
Section: Discussionsupporting
confidence: 92%
“…Our study demonstrated a crucial role for 5-LO in the maintenance of LSCs in AML, confirming recent data in murine models of AML (50). The fact that, in a subset of tumors, the inhibition of 5-LO is able to suppress the tumor stem cell renders feasible a stem cell therapy as a maintenance regimen after induction and consolidation therapy protocols.…”
Section: Discussionsupporting
confidence: 88%
“…We found no significant enrichment of MLL fusion proteins at the promoter region 32 of the ALOX5 locus (Fig. 1e–g).…”
Section: Resultsmentioning
confidence: 75%
“…Enrichment of MLL-N terminal (for both wild-type MLL and MLL fusions), MLL-C terminal (for wild-type MLL), EZH2, SIN3A, H3K27me3 or IgG at the ALOX5 promoter region was shown. Relative to transcription start site of ALOX5 , locations of the three PCR amplicon sites are: ALOX5 -A ( e ): −522~−234 bp; ALOX5 -B ( f ): −259~−79 bp; ALOX5 -C ( g ): +149~+596 bp 32 . * P  < 0.05; ** P  < 0.01, two-tailed t -test. …”
Section: Resultsmentioning
confidence: 99%
“…21 Approximately 5 3 10 7 EML cells were used to perform 2 replicates. High-throughput sequencing was conducted on a Genome Analyzer II (Illumina, San Diego, CA) resulting in 2.7 3 10 7 and 2.6 3 10 7 reads.…”
Section: Chromatin Immunoprecipitation and Sequencingmentioning
confidence: 99%